2001
DOI: 10.1007/s004640000337
|View full text |Cite
|
Sign up to set email alerts
|

Trocar and Veress needle injuries during laparoscopy

Abstract: Background: Inadvertent lesions of the intraabdominal organs and vessels caused by trocars and Veress needles are rare but serious complications of laparoscopic surgery. Establishing the pneumoperitoneum is believed to be the most dangerous step. Methods: The Swiss Association for Laparoscopic and Thoracoscopic Surgery (SALTS) prospectively collected the data on 14,243 patients undergoing various standard laparoscopic procedures between 1995 and 1997. This database was investigated with special regard to intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
104
0
7

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(115 citation statements)
references
References 17 publications
4
104
0
7
Order By: Relevance
“…Schafer et al 8 (2001) analyzed 26 major vascular injuries and reported that only four of them (15%) had been caused by inexperienced surgeons (surgeons who had performed fewer than 50 laparoscopic procedures). The other 22 injuries (85%) had been caused either by experienced surgeons (those who had performed between 51 and 100 procedures) or very experienced surgeons (over 100 procedures performed).…”
Section: Introductionmentioning
confidence: 99%
“…Schafer et al 8 (2001) analyzed 26 major vascular injuries and reported that only four of them (15%) had been caused by inexperienced surgeons (surgeons who had performed fewer than 50 laparoscopic procedures). The other 22 injuries (85%) had been caused either by experienced surgeons (those who had performed between 51 and 100 procedures) or very experienced surgeons (over 100 procedures performed).…”
Section: Introductionmentioning
confidence: 99%
“…This is most notable when the natural scar of the umbilicus is used for the port site. Furthermore, the risk related to the use of ports has been reported in 0.003-0.3% for both vascular and visceral injuries (9).…”
Section: Rationale For Notes and Lessmentioning
confidence: 99%
“…1,2 However, in cases with no history of previous surgery, iatrogenic injury of abdominal viscera, particularly the bladder, from secondary laparoscopic ports is low. 3,4 While previous abdominal or pelvic surgery via a low transverse or low midline incision increases the risk of bladder injury, [5][6][7] this is not a prerequisite for this type of injury. Regardless of the presence or absence of previous surgery, various strategies can be employed to reduce the initial risk on port insertion such as catheterisation immediately prior to surgery.…”
mentioning
confidence: 99%